Kegiatan Penapisan Kesehatan Mental Mengenai Depresi Pada Kelompok Lanjut Usia - Susy Olivia; Alexander Halim Santoso; Alicia Herdiman; Yovian Timothy Satyo; Farell Christian Gunaidi; Edwin Destra (Pusat Riset dan Inovasi Nasional, 2024)
Depression is a common mental disorder in the elderly, associated with emotional distress, increased health care costs, the risk of suicide, and death from other causes. Depression in the elderly is characterised by persistent sadness, helplessness, anhedonia, changes in appetite, sleep disturbances, psychomotor retardation or agitation, fatigue, impaired concentration, and suicidal ideation. Prevalence varies between 7 and 30%, higher in women. Risk factors include bereavement, social isolation, and somatic diseases, which are more common in old age. Depression increases the risk of dementia, morbidity, and mortality, emphasising the need for early screening. This activity uses the PDCA (Plan-Do-Check-Act) method to screen for depression in 61 elderly participants at the Hana Nursing Home using the Geriatric Depression Scale (GDS) questionnaire. The examination results revealed mild, moderate, and severe depression in 8 people (13.11%), 4 people (6.56%), and 2 people (3.28%), respectively. Early detection using GDS is essential for timely intervention, including counselling and medical advice, to improve quality of life and reduce depression-related morbidity and mortality in the elderly population.